Frequency dependence of quantum path interference in non-collinear high-order harmonic generation - 钟诗阳 贺新奎 滕浩 叶蓬 汪礼锋 何鹏 魏志义 (Chinese physics B, 2016)
High-order harmonic generation（HHG） driven by two non-collinear beams including a fundamental and its weak second harmonic is numerically studied. The interference of harmonics from adjacent electron quantum paths is found to be dependent on the relative delay of the driving pulse, and the dependences are different for different harmonic orders.This frequency dependence of the interference is attributed to the spatial frequency chirp in the HHG beam resulting from the harmonic dipole phase, which in turn provides a potential way to gain an insight into the generation of high-order harmonics. As an example, the intensity dependent dipole phase coefficient α is retrieved from the interference fringe.